Analysis of Green Marketing and Viral Marketing on Purchasing Decisions Through Consumer Behavior as an Intervening Variable (Case Study on Nike Shoes in Indonesia) - Wulansari, Rika; Lukitaningsih, Ambar; Fadhilah, Muinah (Dinasti Publisher, 2024)
This study aims to determine the effect of green marketing and viral marketing on purchasing decisions through consumer behavior as an intervening variable (case study on Nike shoes in Indonesia). The research methodology uses quantitative research, non-probability sampling method, and purposive sampling technique. A total sample of 130 respondents was obtained through distributing questionnaires. The results showed that the green marketing variable (X1) had no effect on purchasing decisions (Y). Viral marketing variable (X2) has an effect on purchasing decision (Y). Green marketing variables (X1) affect consumer behavior (Z). Viral marketing variable (X2) affects consumer behavior (Z). Consumer behavior variable (Z) affects purchasing decision (Y). consumer behavior can mediate the relationship between green marketing and purchasing decisions for Nike shoes. Consumer behavior can also mediate the relationship between viral marketing and purchasing decision for Nike shoes.